PERAN GURU UNTUK MENGEMBANGKAN KREATIVITAS ANAK MELALUI MEDIA BAHAN ALAM - Sartika, Tri; Aunurrahman, Aunurrahman; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2023)
This study aims to determine the role of teachers in developing children's creativity through the media of natural materials at Raudhatul Athfal Dharma Wanita. The research method used is qualitative in the form of descriptive research. The subjects in this study were children and teachers of group B1. The research location in this research is at Raudhatul Athfal Dharma Wanita Balai Karangan, Jalan Pangeran Pati. Data collection techniques through observation, interviews and documentation. Research results 1. The teacher's role as an educator is that the teacher only provides one tasting activity. Teachers need to add variety, methods in learning, teachers give assignments to children according to directions and rules. 2. The role of the teacher as a role model or role model, namely the teacher familiarizes children with maintaining the cleanliness of the classroom and the surrounding environment. 3. The teacher's role as a facilitator is to provide worksheets and colored pencils, tempura paint, banana fronds and star fruit. 4. The teacher's role as a mediator is a tasting activity. The teacher turns the child's learning atmosphere on by singing